Free Radical Scavenging Activity of Chromolaena odorata L. Leaves - Maulida, Putri Anni; Putri, Devi Anggraini; Fatmawati, Sri (IPTEK The Journal for Technology and Science, 2025)
Chromolaena odorata is one of the plants used by the community as traditional medicine. Some of the community in Ambon, Indonesia use C. odorata leaves as wound medicine. This study aims to evaluate free radical scavenging activity from fractions of methanol extract of C. odorata. Methanol extract of C. odorata leaves is known to have good free radical scavenging activity. The fractionation from methanol extract of the C. odorata leaves obtained fractions A through E, where fractions C, D, and E showed inhibitory activity against DPPH radicals (2,2-diphenyl-1-picrylhydrazyl) with IC50 values of 63.95, 64.38, and 202.15 micrograms per milliliter, respectively. The positive control, which is gallic acid, has an IC50 value of 5.29 micrograms per milliliter.